2021
DOI: 10.1126/sciimmunol.abf6692
|View full text |Cite
|
Sign up to set email alerts
|

Clonal expansion and activation of tissue-resident memory-like T H 17 cells expressing GM-CSF in the lungs of patients with severe COVID-19

Abstract: Hyperinflammation contributes to lung injury and subsequent acute respiratory distress syndrome (ARDS) with high mortality in patients with severe coronavirus disease 2019 (COVID-19). To understand the underlying mechanisms involved in lung pathology, we investigated the role of the lung-specific immune response. We profiled immune cells in bronchoalveolar lavage fluid and blood collected from COVID-19 patients with severe disease and bacterial pneumonia patients not associated with viral infection. By trackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
173
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(187 citation statements)
references
References 55 publications
6
173
0
8
Order By: Relevance
“…Recent studies have demonstrated that Th17 cells could acquire a tissue-resident phenotype in the lungs (Amezcua Vesely et al, 2019). Based on the gene sets obtained from a previous research (Zhao et al, 2021), we calculated the residency and migratory scores of Th17 cells and found that the Th17 cells in our study have a relatively higher residency score (Figure 3G), suggesting that Th17 cells might exhibit the phenotype of tissue-resident memory-like Th17 cells (Trm-like 17 cells).…”
Section: Expansion Of Clonal Tissue-resident Memory-like Th17 Cellsmentioning
confidence: 55%
See 1 more Smart Citation
“…Recent studies have demonstrated that Th17 cells could acquire a tissue-resident phenotype in the lungs (Amezcua Vesely et al, 2019). Based on the gene sets obtained from a previous research (Zhao et al, 2021), we calculated the residency and migratory scores of Th17 cells and found that the Th17 cells in our study have a relatively higher residency score (Figure 3G), suggesting that Th17 cells might exhibit the phenotype of tissue-resident memory-like Th17 cells (Trm-like 17 cells).…”
Section: Expansion Of Clonal Tissue-resident Memory-like Th17 Cellsmentioning
confidence: 55%
“…Genes of CD4 + T cells' residency and migration were obtained from previous studies (Zhao et al, 2021), then were converted into mouse genes using the Mouse Genome Informatics Database (Supplementary Table 1; Blake et al, 2017). The AddModuleScore function in Seurat was used to calculate the CD4 + T cells' residency and migration scores.…”
Section: Analysis Of Cd4 + T Cells' Residency and Migration Scoresmentioning
confidence: 99%
“…More recently, Thwaites, RS et al discovered a progressive elevation of GM-CSF, CXCL10/IP-10 and IL-6 levels in some COVID-19 patients with severe thrombosis (Thwaites et al 2021 ). Although IL-6 was equally elevated both in patients with COVID-19 or non-COVID-19 (e.g., influenza), only GM-CSF was prominently elevated in patients with severe COVID-19 (Thwaites et al 2021 ), supporting the notion that GM-CSF serves as an important biomarker of COVID-19 disease severity (Hue et al 2020 ; Gibellini et al 2020 ; Blot et al 2020 ; Thwaites et al 2021 ; Zhao et al 2021 ).…”
Section: Introductionmentioning
confidence: 80%
“…In response to severe SARS-CoV-2 infections, some hosts mount hyperactive inflammatory responses characterized by the excessive infiltration and activation of myeloid cells and consequent production of various cytokines and chemokines – the “cytokine storm” (Qiang et al 2021 ). GM-CSF might be a key mediator of SARS-CoV-2-induced cytokine storm in a subset of COVID-19 patients with severe outcomes (Hamilton, 2020 ; Hue et al 2020 ; Gibellini et al 2020 ; Blot et al 2020 ; Thwaites et al 2021 ; Zhao et al 2021 ). On the one hand, GM-CSF can promote myelopoiesis as well as recruitment of innate immune cells (e.g., monocytes, macrophages and dendritic cells) to SARS-CoV-2 infection sites (Hamilton, 2020 ; Qiang et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, elevated IL-17A and GM-CSF protein in the serum of patients with COVID-19 have been associated with a more severe clinical course. Collectively, our study suggests that lung Trm17 cells are a potential orchestrator of severe COVID-19 hyperinflammation [ 82 ].…”
Section: Th17 Cells In Viral Infectionsmentioning
confidence: 99%